Analisa Kualitas Daya Listrik Instalasi Wing Amerta RSUP Sanglah Denpasar - Meyyasa, Putu; Hartati, Rukmi Sari; Manuaba, Ida Bagus Gde (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi Elektro, 2019)
The Amerta Wing Installation is part of Sanglah General Hospital Denpasar, which has outpatient / polyclinic services, inpatient care, delivery rooms, operating rooms, and support services to facilitate the needs of the people who want more comfortable services, was inaugurated and opened on December 30, 2004 as the realization of the people's dream to have an international hospital in Bali. Electricity consumption in 2016, 2017 and 2018 is 1,390,145,617 rupiah. From the total cost of energy expenditure as a whole, there is an excess consumption cost of reactive power (KVARh) of 199,578,425 rupiah, with an annual average of 66,526,141 rupiahs and a monthly average of 5,543,845 rupiah. Electricity consumption comes from 4 equipment groups, namely: air conditioning equipment group which is equal to 76.34% followed by other equipment groups of 17.22%, medical equipment group of 3.23%, the lowest consumption is in the lighting group of 3.21%. Electric power quality is very important to note because it can maximize the available power and maintain the security level of the equipment used in patients. The results of the analysis, measurement and calculation showed that the power capacity of 555KVA with cosphi of 0.75 requires a power factor improvement to be 0.98 with the installation of bank capacitors with a capacity of 285.575 KVAR. y taking into account the availability of bank capacitors on the market and spare power by 40%, the required bank capacitors are 400KVAR. This investment will return to 1.8 years and after the second year and so on, is the profit or efficiency of hospital expenditure of Rp. 5,543,845, - every month or Rp. 66,526,141, - every year, and is expected to: Maximize power consumption (KVA), avoid overloading the transformer (overload) and avoid increasing current / temperature on the cable. Keywords: Power Quality, Cosphi, Capacitors Bank, Hospital Efficiency.